Poverty / Inequality Nexus Microfinance: Case of Nepal (Socio-Economic Development Panorama, 2008)
Poverty / inequality lessening activities is a tough task for developing countries. Developing countries are effortful to lessen the level of poverty intensively from 1980s decades. They used Micro Finance (MF) as one of the corrective devices for this purpose. Countries with agro-set up have more incidence of poverty than that of countries with industrial or service sector domination. Despite various efforts, Nepal still has high incidence of poverty with inequalities. This scenario is found to be varied among the regions / geographical zones / districts. Nepalese are involved in poverty lessening efforts through MF in relation to rural financing. Despite all these efforts outreach up to the ultra poor has come from trickle down efforts from Micro Finance Institutions (MFIs). Institutional credit delivery has reached up to 20-30 percent population. There is predominance of poorest of the poor in remote rural areas of Nepal. How to reach up to these segment through MF activities is a challenging task for state facilititators and even MFIs in Nepal. Underdevelopedness and remoteness has hindered for more outreach from MFIs on behalf of the poor and destitute people. Tax exemption, subsidies, etc. to MFIs would upgrade capacity and expansion of outreach is possible. Introducing poor centric rural MF program on the part of MFIs could lessen the culture of poverty / inequality in Nepal. For this, an indegenous MF program matched with socio-cultural settings could be desirous for rural areas. Keywords: microfinance, MF, poverty inequality, socio-economic betterment, modalities of microfinance, cost related, self-help groups Socio Economic Development Panorama, Vol. 1, No. 3(2008) pp. 147-158